2017
DOI: 10.1155/2017/3013249
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of the Lunar Penetrating Radar and Investigations of the Geological Structures of the Lunar Regolith Layer at the Chang’E 3 Landing Site

Abstract: In the process of lunar exploration, and specifically when studying lunar surface structure and thickness, the established lunar regolith model is usually a uniform and ideal structural model, which is not well-suited to describe the real structure of the lunar regolith layer. The present study aims to explain the geological structural information contained in the channel 2 LPR (lunar penetrating radar) data. In this paper, the random medium theory and Apollo drilling core data are used to construct a modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Similar procedure has been applied for the CE‐3 LPR data in previous studies (e.g., Lai et al, 2017). Based on a regolith model that contains stochastically distributed relative permittivity around a given average value (Ding et al, 2017), the effect of h LPR on the derived relative permittivity based on hyperbolic echo patterns is constrained to be ~13% (see Figure S8), which is comparable with the inherent uncertainty associated with the general method (Shihab & Al‐Nuaimy, 2005).…”
Section: Geological Context Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar procedure has been applied for the CE‐3 LPR data in previous studies (e.g., Lai et al, 2017). Based on a regolith model that contains stochastically distributed relative permittivity around a given average value (Ding et al, 2017), the effect of h LPR on the derived relative permittivity based on hyperbolic echo patterns is constrained to be ~13% (see Figure S8), which is comparable with the inherent uncertainty associated with the general method (Shihab & Al‐Nuaimy, 2005).…”
Section: Geological Context Data and Methodsmentioning
confidence: 99%
“…Similar modeling work has been carried out to analyze the thickness and interior structures of lunar regolith at the CE-3 landing site, and possible dielectric permittivity of the subsurface materials was derived using 10.1029/2019EA000862 inverse calculation (Ding et al, 2017;Lai et al, 2017;J. Li et al, 2017).…”
Section: Numerical Simulation Of the Lprmentioning
confidence: 99%
“…Thus, we established two different stochastic models with fewer and more horizontal disturbances, respectively, as shown in Figure 4c,d. Here, we applied the stochastic modeling method to simulate the lunar regolith, which is closer to the real situation according to the statistic [22,41]. Previous works have applied this method both in the GPR and LPR numerical simulations [41][42][43].…”
Section: Stochastic Modelingmentioning
confidence: 99%
“…However, in the past, the lunar regolith has usually been assumed to be a uniform layered medium [4][5][6][7][8]. A series of recent studies have shown that the lunar regolith is essentially inhomogeneous [9][10][11][12][13][14][15][16] but the specific structural characteristics of the lunar regolith are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Most traditional numerical simulations of LPR data assume layered models [4][5][6][7][8] and cannot well represent the heterogeneity of the lunar regolith. Recently, several works have considered the heterogeneity [9][10][11][12][13][14][15] but do not take typical models into account (e.g., cracks and ejecta). Lv et al [16] constructed four typical models and performed numerical simulations using the time-domain finite-difference method, which can better present the wave propagation in the lunar regolith with strong heterogeneity.…”
Section: Introductionmentioning
confidence: 99%